The Apennines: Tectonics, Sedimentation, and Magmatism from the Palaeozoic to the Present - Liotta, Domenico; Molli, Giancarlo; Cipriani, Angelo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Apennine orogenic system is a natural laboratory for multidisciplinary and integrated studies. The evolution of the Apennines is framed by the fragmentation of Pangea and the development of the Tyrrhenian Basin. Thus, the Apennines have carried this memory from the Permian and Triassic-Early Jurassic rifting, to the Oligocene-Miocene collision, and finally to the Miocene-Present, during which extension and compression have progressively migrated eastwards. Magmatism, hydrothermalism, and sedimentation in the Apennines have accordingly evolved in time and space. In this Special Issue, multidisciplinary and integrated studies have been published improving our knowledge of the Apennines and discussing: (a) the development of deformation and metamorphism in different tectonic environments, from the rifting stage to the subduction, exhumation, and late-orogenic stages; (b) the Meso-Cenozoic tectono-stratigraphic evolution of sedimentary basins, and their role in the Apennine orogeny; (c) the thermochronological evolution of sedimentary units and the dating of deformation episodes through geochemical techniques; (d) the magmatism and its connection to geodynamic evolution, from the mountain chain to the Tyrrhenian Basin; (e) recent tectonics, as reconstructed through seismological and paleo-seismological studies; and (f) the crustal structure, as derived by geophysical methods and their interpretation.